Comparison of Restrictive Vs Routine Episiotomy And Its Outcome in Tertiary Care Hospital - Butt, Alveena; Fatima, Col Dr Yasmin; Noor, Lt Col Lubna; Gul, Muhammad Taimoor; Majeed, Major Sadia; Arif, Major Maryam; Rasheed, Faisal (Medical Journal of South Punjab, 2025)
Objective: The purpose of this study is to examine the differences and similarities in outcomes that occur when restrictive episiotomy and routine episiotomy are performed on first-time mothers who are giving birth vaginally at the same time.Methods: For the purpose of determining the effects of employing a restrictive episiotomy approach in comparison to the standard application of episiotomy, a prospective cohort study was carried out. In order to establish two distinct cohorts, a total of one hundred women who were experiencing their first pregnancy and were presenting in the labor room with either spontaneous labor or labor that had been induced were recruited. The evaluations between two groups were carried out throughout the entirety of the labor process, immediately following the postpartum period, and on the very first day after the birth of the baby, and the data were tabulated and analyzed in a systematic manner.Results: In the routine episiotomy group, 14% of primigravidae experienced vaginal and paraurethral tears, while the restrictive episiotomy group exhibited a slightly higher rate of 22.22%, with no statistically significant association observed. Perineal tears were observed in 15.55% of cases in the restrictive group, while episiotomy extension was observed in 26% of cases in the routine group. However, there was no statistically significant association between the occurrence of perineal tears and episiotomy extension. Due to the fact that 64.45% of patients in the restrictive group gave birth without any damage to the perineum, there was a significantly lower requirement for suturing in the restrictive group (20%) compared to the routine group (100%).Conclusion: The results of this study provide substantial evidence suggesting that the immediate outcomes that follow the utilization of a routine episiotomy are not superior to those that are achieved through the utilization of a restrictive approach. Indeed, routinely employing episiotomy can have adverse effects, as it may subject certain women to surgical incisions and result in more harm than if they had experienced less injury.